UE5 simulation methodology for autonomous uav swarms: multi-agent learning and communication resilience assessment in emergency scenarios - Nazarenko, V.; Zazymko, O. (Energy and Automation, 2026)
The article discusses an approach to building a pilot simulation environment in Unreal Engine 5 to study the behavior of a swarm of unmanned aerial vehicles in emergency response tasks. The relevance of the work stems from the fact that when searching for people, inspecting damaged areas, and avoiding obstacles, communication between devices can be unstable, and centralized control schemes can become inefficient. The study aims to develop a simplified UE5-oriented methodology that enables setting mission scenarios, simulating packet loss, latency, and short periods of communication failure, and collecting telemetry data to compare control approaches. The technique is based on a modular plugin architecture that includes Scenario Runner, Agent Framework, Communication Stress Injector, Role Manager, and Telemetry Logger. Four scenarios are proposed for the initial analysis: covering the open area, searching for targets in the urban environment, avoiding obstacles in the ruin corridor, and a mixed search-and-return mission. The result is a data structure, a set of metrics, and a simulation example of evaluating mission success, execution time, number of collisions, communication quality, and recovery from a stressful window. The proposed approach does not replace field testing, but creates a basis for early validation of ideas and preparation for further hardware validation. Recieved: 20.03.2026. Recieved: 03.06.2026. Accepted: 22.06.2026